Petrophysical log responses of a core-drilled from the granite-gneiss complex of the Rio Negro Magmatic Arc (Neoproterozoic of Rio de Janeiro State, Southeastern Brazil) - Louback, Viktor Souto; Dal’ Bó, Patrick Führ; Novaes, Pedro Henrique Alves; Almeida Paula, Caio; Carvalho, Caio Almeida; Braga, Marco Antônio; Barros, João Paulo Porto; Gama, Maria Filipa Perez; Souza Cunha, Alan (Journal of applied geophysics, 2025)
In many exploration projects, drill cores are not always recovered due to the high costs involved in drilling, recovering and storage. In some cases, the benefits of core recovery outweigh the costs and limitations, while in others it may be more advantageous to use alternative methods to obtain relevant information about the drilled hole. This study presents a vertical succession of rocks from the Rio Negro Magmatic Arc that are not normally seen because drill cores are rare and areas with vertical outcrops are difficult to access. The aim of this study is to correlate the petrophysical data measured in the UFRJ-01-RJ borehole with the geological features observed in the drill core in order to generate electrical facies that can be applied to other boreholes. In this work, wireline logging was carried out using optical and acoustic televiewers as well as bulk density, gamma ray and caliper. The rocks from borehole UFRJ-01-RJ belong to the Rio Negro Complex and returned 39.6 m of a sequence of orthogneisses interbedded with granites and pegmatites. Six main lithotypes were identified in the profiles based on differences in color, grain size, texture and fracture, which were easily recognizable in the core. The caliper profile shows practically no variations, as the gneisses are little altered. The bulk density showed only slight fluctuations throughout the borehole recording an average value of 2.62 g/cm3. The optical televiewer proved to be very useful for observing differences in color, grain size and orientation of the foliation, while the acoustic televiewer identified fracture zones and textural differences in the rocks. The bulk density and natural gamma ray values were found to be inversely proportional for most of the rocks in borehole UFRJ-01-RJ. This is due to the different mineralogy of the rocks, which alternate between mafic portions (with higher density and lower potassium content) and felsic portions rich in K-feldspar (with lower density and higher potassium content). The analysis of the different electrical facies patterns obtained with optical and acoustic televiewers made it possible to draw up a facies table of the main lithotypes described. These image features, in combination with gamma ray and bulk density profiles, proved to be of high value in identifying the lithotypes. Therefore, the geophysical tools used herein can equalize the lack of drill cores in many geological studies even for when applied for lithologies not commonly studied by geophysical methods. •Integrated geophysical data identified six lithotypes in UFRJ-01-RJ well•Fractures and foliation patterns mapped using acoustic and optical image logs.•Bulk density and gamma profiles highlight mafic-felsic mineralogical alternations.•Image logs combined with gamma ray and density profiles can identify the lithotypes.•The geophysical tools used herein can equalize the lack of drill cores.